2023
DOI: 10.1021/acsabm.3c00425
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of ZnO/CuO Nanocomposites Using Parsley Extract for Potential In Vitro Anticoccidial Application

Samir Mustafa Hamad,
Azeez Abdullah Barzinjy,
Raghda Rafigh
et al.

Abstract: In this study, a simple, low-cost, and environmentally friendly method for the green synthesis of ZnO/CuO nanocomposites (NCs) using parsley extract was developed. The phytochemical components in the parsley leaf extract reacted with precursor salts in solution and yielded ZnO/CuO NCs. The synthesis of the green-synthesized NCs was confirmed via various characterization techniques, including UV−vis spectroscopy, X-ray diffraction (XRD) analysis, energy-dispersive X-ray (EDX), transmission electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…1c). 17 The structural illustration of the synthesized material was further studied through the Rietveld analysis. Subsequent Rietveld refinement facilitated the identification of the phase fraction of CuO and ZnO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c). 17 The structural illustration of the synthesized material was further studied through the Rietveld analysis. Subsequent Rietveld refinement facilitated the identification of the phase fraction of CuO and ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…2d). 17 From the plot of partial density of states (PDOS), it was observed that the metal 3d and O 2p-orbitals contributed maximum near the Fermi level for both CuO 25 and ZnO 26 (Fig. 3a and b).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 98%